Gas Phase Deposition of Trichloro(1H,1H,2H,2H-perfluorooctyl)silane on Silicon Dioxide, by XPS - Lee, Michael V. (2012)
Monolayers of trichloro(lH,1H,2H,2H-perfluorooctyl)silane, Cl3SiCH2CH2(CF2)5CF3, were deposited via chemical vapor deposition onto the native oxide layer on silicon after plasma-cleaning. The samples have high hydrophobicity, and provide a valuable comparison to perfluorinated alkyl silane layers obtained by liquid deposition. Gas-phase deposition of perfluorinated alkyl silanes is a useful means for reducing stiction in micro- and nano-electromechanical systems, which have narrow spaces that can trap bubbles and prevent liquid-based silane passivation.